2002
DOI: 10.1021/jp015618p
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Interchain Excitations in Conjugated Polymers:  Spatially-Varying Interfacial Solvatochromism of Annealed MEH-PPV Films Studied by Near-Field Scanning Optical Microscopy (NSOM)

Abstract: The nature of interchain electronic species in conjugated polymers has been the subject of much debate. In this paper, we exploit a novel near-field scanning optical microscopy (NSOM)-based solvatochromism method to spatially image the difference in dipole moment, and hence the difference in degree of charge separation, between the ground and electronic excited states of the emissive interchain species in films of poly(2-methoxy-5-(2′-ethylhexyloxy)-1,4-phenylene vinylene) (MEH-PPV). The method uses NSOM to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 66 publications
3
70
0
4
Order By: Relevance
“…It is however noted that some authors have also reported similar values 28,29 to the ones presented in this work. A possible contribution from a fluctuating permanent dipole associated with the presence of alkoxy side chains may account for the larger values, although a more detailed study is needed to establish the exact nature of any possible sidechain contribution.…”
Section: Ac and DC Electrical Characterizationsupporting
confidence: 90%
“…It is however noted that some authors have also reported similar values 28,29 to the ones presented in this work. A possible contribution from a fluctuating permanent dipole associated with the presence of alkoxy side chains may account for the larger values, although a more detailed study is needed to establish the exact nature of any possible sidechain contribution.…”
Section: Ac and DC Electrical Characterizationsupporting
confidence: 90%
“…O acoplamento vibrônico em polímeros orgânicos conjugados segue as mesmas regras de seleção que as de moléculas orgânicas luminescentes [104][105][106] . Isto quer dizer que serão acoplados os modos normais que apresentam simetria que leve a uma representação irredutível totalmente simétrica do integrando do operador no momento de dipolo de transição.…”
Section: Propriedades Fotofísicas Dos Polímeros Eletroluminescentesunclassified
“…A relação observada de intensidades entre as bandas vibrônicas relaciona-se diretamente com os acoplamentos vibrônicos, mostrando que a probabilidade de transição entre os níveis ocorre de acordo com o Princípio de Franck-Condon [107][108][109] . O parâmetro que quantifica a probabilidade de transição entre os níveis vibrônicos e relaciona a energia de relaxação entre estados vibrônicos a uma dada temperatura com a freqüência de acoplamento elétron-fônon é o de Huang-Rhys [98][99][100][101][102][103][104][105][106][107][108] .…”
Section: Propriedades Fotofísicas Dos Polímeros Eletroluminescentesunclassified
See 2 more Smart Citations